Pengaruh Iklan Televisi Terhadap Perilaku Memilih Produk Hand Phone (Hp) (Studi Terhadap Pemuda Di Kelurahan Pandan Kasturi, Kota Ambon) - Rumra, Fatmawati (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2020)
This research is motivated by the existence of consumptive behavior in choosing HP products by youth in Ambon City which was carried out in Pandan Kasturi Village, Ambon City, with the aim of knowing and analyzing the understanding of youth thinking related to the behavior of choosing HP products on the consumptive lifestyle of youth. The type of research used is quantitative. The data obtained was carried out through 1. Literature study, namely information obtained through reference books, documents, and sources relevant tothe study being studied. 2. . Questionnaires are written questions that have been prepared to be given to respondents in order to get responses or information through a survey method by taking a sampleof 76 male and female youth respondents. The data analysis technique used is Product Moment Correlation analysis, with the SPSS V.13.0 program. for windows. The results of the research by testing the correlation(relationship), where the results obtained that there is a positive relationship on the influence of television advertising on the behavior of choosing HP products in Pandan Kasturi youth, Ambon City is 0.296